Longitudinal effects of systemic inflammation markers on periodontitis - Pink, Christiane; Kocher, Thomas; Meisel, Peter; Dörr, Marcus; Markus, Marcello R. P.; Jablonowski, Lukasz; Grotevendt, Anne; Nauck, Matthias; Holtfreter, Birte (Journal of clinical periodontology, 2015)
Aim Systemic low‐grade inflammation represents a central hallmark of chronic diseases and has been proposed as the underlying mechanism linking factors like obesity or diabetes with periodontitis. However, the impact of inflammatory markers on periodontitis has not yet been investigated. Materials and Methods The study population comprised 1784 subjects from the Study of Health in Pomerania with complete 11‐year follow‐up. Fibrinogen and white blood cell (WBC) counts were measured as markers of inflammation. Periodontitis was assessed by probing depth (PD), clinical attachment loss (CAL) and the CDC/AAP case definition. Results Multilevel regression analyses revealed significant coefficients for the impact of both inflammation markers on the percentage of sites with PD/CAL ≥ 3 mm. Increases in fibrinogen about 1 g/l were associated with 3.0% and 2.7% more sites with PD/CAL ≥ 3 mm respectively. Consistent associations were found using mean values of PD/CAL but not using missing teeth or caries. Regarding the CDC/AAP case definition, 11‐year changes in fibrinogen and WBC counts were significantly associated with ≥1 category progression (OR: 1.36 and 1.11). Conclusions Fibrinogen levels and WBC counts showed consistent long‐term associations with PD, CAL and the CDC/AAP case definition. Results indicate that systemic low‐grade inflammation might indeed represent one possible pathway for effects of obesity, diabetes or other chronic inflammatory conditions on periodontitis.